A Theoretical and Simulation Performance Study of Hydraulic Electric Energy Regenerative Shock Absorber - Yasin, Faisal; Fangwei, Xie; Mujtaba, Muhammad; Ali, Asad; Khan, Muhammad Rizwan (Journal of Advance Research in Mechanical and Civil Engineering (ISSN: 2208-2379), 2018)
To enhance the fuel economy of automobile and extend the thermal fatigue duration of the typical shock absorbers, energy regenerative shock absorbers have enticed huge attention. Hydraulic electric energy-regenerative shock absorber (HERSA) is a new kind of shock absorber which can regenerate an amount of energy, dissipated as the heat energy in traditional shock absorber. This paper briefly describes HERSA’s working principle, uses AMESim (hydraulic simulation software) to get damping attribute of HERSA as properly as conventional shock absorber through some theoretical and simulation tests. On the basis of simulation outcomes, we differentiate the hydraulic electric energy regenerative shock absorber (HERSA) and traditional shock absorber, and the results revealed that the inclusive performance of the prior is higher to that of the recent, but it shows the theoretical possibilities of HERSA’s structure to improve fuel economy and ride comfort.